The Role of Electronic Platforms in the Professional Preparation of Early Childhood Education (female) Students. (Damascus University Journal of educational and Psychologyical sciences, 2025)
The aim of the current research is to explore the role of electronic platforms in the professional preparation of third-year female students majoring in Early Childhood Education. To achieve this goal, the researcher followed a descriptive survey methodology and prepared a questionnaire consisting of two sections: the first section included personal data, while the second section comprised 36 items distributed across four dimensions (cognitive, skill-based, emotional, and social). The sample consisted of 196 female teacher students in their third year specializing in Early Childhood Education. The study results revealed that the role of electronic platforms in the professional preparation of female teachers was significant. The cognitive dimension ranked first, followed by the skill-based, social, and finally the emotional dimension.
Keywords: E-Learning; Educational Platforms; Professional Preparation; Female Teacher; Early Childhood Education